Field investigation on operation parameters and performance of air conditioning system in a subway station. Issue 1 (January 2020) - Li, Yuan; Zhang, Quan; Wang, Jiaqiang; Yue, Chang; Che, Lunfei; Zhao, Jianwei; Wang, Yanhua; Duan, Fei
Ventilation and air conditioning system in subway stations accounts for about 50% of the total energy consumption of the subway stations. The energy consumption ratio of public area to equipment room is about 6.5:3.5. In order to understand the energy saving potential of public areas and equipment rooms, a field measurement for a typical subway station in central China was conducted from 19 to 29 September 2018. The field testing parameters include weather conditions, indoor air temperature and humidity, supply and return air flow rate, chilled water temperature, and flow rate. Meanwhile, some parameters recorded by the system control panel, such as pump frequency, chiller power demand, and energy consumption, were also collected. The paper studied the operating characteristics of the ventilation and air conditioning system and the cooling load pattern of the subway station, focusing on the following three aspects: cooling capacity and power demand of the chiller under different conditions, dynamic cooling capacity of the air handling units, and cooling load characteristics of the equipment rooms. Different operation conditions influence the operation of chiller. It was found that the real power demands under two operation conditions, i.e. minimum and all fresh air modes, are 121 and 77 kW, and the corresponding coefficient of performances are 4.33 and 4.77, respectively. The actual cooling capacity at night is about 80% that of the daytime, and is about 40% of the design value, which indicates that the air handling units operate under partial load. During the testing period, the actual cooling load is about 10–50% of the design load, of which 50–95% is sensible cooling load. These data can help readers understand the overall situation of a typical subway station adequately and provide numerical basis for energy saving optimization of the ventilation and air conditioning system.